Tracing bottom water oxygenation with sedimentary Mn/Fe ratios in Lake Zurich, Switzerland - Naeher, Sebastian; Gilli, A.; North, R.; Hamann, Y.; Schubert, C. (Elsevier Science BV, 2013)
Redox dynamics of manganese (Mn) were studied in the sediment of Lake Zurich using precise sediment core age models, monthly long-term oxygen (O2) monitoring data of the water column (1936–2010) and high-resolution XRF core scanning. The age models were based on bi-annual lamination and calcite precipitation cycles. If present, Mn exhibits distinct maxima, which coincide with the annual maximum deep-water O2 concentrations in spring according to the monitoring data. In contrast, the iron (Fe) signal is mainly the result of calcite dilution, as indicated by a strong negative correlation between Fe and calcium (Ca) XRF data. The Mn/Fe ratio in the core from the maximum lake depth (ZH10-15, 137 m) revealed a moderate correlation with O2 measurements in the lake bottom water confirming the successful application of the Mn/Fe ratio to semi-quantitatively reconstruct bottom water oxygenation in the lake. Mostly low ratios were observed between 1895 and the mid-1960s as a result of eutrophication. However, geochemical focusing and sedimentological factors can reduce the applicability of the Mn/Fe ratio in reconstructing O2 concentrations in the bottom water of lakes.